Rapid reporting of urine culture results: Impact of the uro-quick screening system - (:unkn) unknown (My University, 2010)
This study evaluated the impact of the Uro-Quick (UQ) screening system (Alifax, Italy) for a rapid and accurate reporting of urine cultures, and whether it can provide bacterial yield to be used in identification and susceptibility testing. A total of 1480 urine samples collected between October 2006 and July 2008 were tested by conventional culture (CC) methods and UQ simultaneously. Sediments of positive UQ vials were used as bacterial yields for identification and susceptibility testing procedures. Of the 1480 samples, 999 revealed bacteria and/or leukocytes in direct microscopy. Among diese 999 samples, positive growth was detected in 420 (42%) and 433 (43.3%) by UQ and CC, respectively. However, only 0.6% of samples without bacteria and leukocytes exhibited positive growth. When compared to CC, UQ demonstrated high levels of positive predictive value (95.9%), negative predictive value (94.8%), sensitivity (93%) and specificity (96.9%). Both CC isolates and UQ bacteria showed 81.3% concordance in identification results. Susceptibility testing of UQ bacteria displayed >90% agreement, when compared with standardized disk diffusion test. Our results indicate that UQ can reliably be used in routine laboratories giving microbial growth results in 3 hours. The most significant part of the study is that bacterial yields of UQ positive samples can be used in identification and susceptibility testing, allowing a rapid, same-day reporting of urine cultures.
Keywords: Rapid reporting; Urine culture; Uro-quick